In situ deformation analysis of Mg in multilayer Mg-steel structures. (5th April 2017) - Sadeghi, Alireza; Inoue, Junya; Kyokuta, Nobuhiko; Koseki, Toshihiko
Abstract: The deformation modes of Mg in a steel-Mg-steel multilayer composite were studied by step-by-step deformation and EBSD for the same region at 0, 20 and 30% deformation. Texture evolution was characterized using pole figures. The results indicate that the basal texture intensity significantly increases up to 20% deformation. However, from 20% to 30% deformation, activity of prismatic slip increases and the intensity of the overall basal texture is reduced. Shear stress and Schmid factor analysis of the multilayer system showed the probability of prismatic slip increases up to 35% by increasing the stress ratio up to 0.4 and decreases afterwards. Graphical abstract: Highlights: SS-Mg-SS three layer samples were made by reactive transient liquid phase bonding. Texture & slip activity were studied by In-situ EBSD at consecutive strain levels. Orientation evolution confirms higher activity of non-basal slip at high strains. Effect of stress biaxiality on shear stress ratio of slip systems was studied. Biaxiality increases probability of prismatic slip up to the stress ratio of 0.4.